Conceptualization of the phenomenon of the mental model of the world in cognitive-behavioral and narrative psychotherapy - ABRAMOV, Volodymyr (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2024)
This article analyzes the conceptualization of the phenomenon of the mental model of the world, which mediates behavior, in A. Beck's cognitive therapy, J. Young's schema therapy, functional contextualism, and narrative therapy by M. White and D. Epston.In A. Beck's classic cognitive therapy, this phenomenon is conceptualized within the framework of "schema." Cognitive therapy emphasizes the cognitive nature of schemas and proposes only cognitive methods for their correction.In J. Young's schema therapy, the concept of schemas pertains not only to the cognitive sphere of personality but also to emotional experiences, bodily sensations, and easily activates memories in which it was formed. Accordingly, schema therapy offers emotionally oriented techniques, such as imaginative rescripting and the chair technique, alongside cognitive techniques.In M. White's narrative therapy, the concept of narrative is utilized as a means for individuals to interpret their life events and construct their worldview and identity. The narrative therapist assists individuals in crafting a narrative that aligns with their values, highlighting unique life episodes that challenge their existing narrative.In functional contextualism and behavioral therapy, the concept of rule-governed behavior is employed. Rules can be learned directly through experience or indirectly through derived verbal relations. The behavioral therapist's work focuses on modifying the rules that govern behavior by changing the context in which the individual's behavior occurs.The article emphasizes that despite the different conceptualizations of the phenomenon of the mental model of the world, which is formed in individuals and mediates their behavior, the analyzed approaches, although differing in theoretical and methodological positions, utilize similar mechanisms for modification. Specifically, behavioral experiments in A. Beck's cognitive-behavioral therapy and the limited reparenting style and imaginative rescripting of J. Young's schema therapy can be seen as changes in the context of the individual's behavior that lead to correcting the governing rules. Conversely, the various conceptualizations of the mental model phenomenon enrich the therapist's arsenal of techniques.
Keywords: cognitive-behavioral therapy; narrative psychotherapy; relational frame theory; functional contextualism; schema therapy